Etnobotani Masyarakat Lokal, Struktur Anatomi Jenis Pandan (Pandanaceae) Bermanfaat di Jawa Timur - Jati Batoro; Serafinah Indriyani; Brian Rahardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2015)
Along with the development of culture, both traditional and biotechnology, the use of pandan, as can be found either in the community, traditional markets, experiencing a shift which was replaced by other materials, such as by plastic straps, caps from fabric. Ethnobotany study done by collecting a